Seasonal variations in posttraumatic wound infections after open extremity fractures. Issue 6 (December 2015) - Sagi, Henry Claude; Cooper, Seth; Donahue, David; Marberry, Scott; Steverson, Barbara
Abstract : BACKGROUND: The vast majority of the orthopedic trauma literature has dealt with risk of infection as a function of time to debridement and severity of open fracture. The goal of this analysis was to determine if either the incidence or causative organism of posttraumatic infection varies with the season in which the open fracture occurred. No such study has been previously published. METHODS: This is a retrospective chart review of all skeletally mature patients sustaining an open fracture of either the upper or the lower extremity long bones from 2007 to 2012. Charts were reviewed to extract information regarding date of injury, Gustilo-Anderson grade of open fracture, Injury Severity Score (ISS), time to surgical debridement, any posttraumatic wound infection (deep or superficial), and the causative organisms. Patients were placed into one of four groups based on the time of year: spring (March to May), summer (June to August), fall (September to November), and winter (December to February). Patients were excluded if they were skeletally immature, smokers, or also diagnosed with a condition that would increase risk of infection. Statistical analysis was performed to assess whether any observed differences were of significance. RESULTS: All four groups were similar with respect to Gustilo grade, ISS, and time to surgical debridement. A total of 1, 128 open fractures were treated between 2007 and 2012. There were 58 total infections for an overall incidence of 4.3%. The incidence of infection based on season was 6.0% for spring, 4.9% for summer, 2.8% for fall, and 3.6% for winter ( p < 0.05). The incidence of infection was 5.5% for spring and summer combined and 3.9% for winter and fall combined ( p < 0.05). Gram-positive organisms were more prevalent in the spring and summer seasons ( p < 0.05). Although gram-negative organisms were cultured more commonly in the fall and winter seasons (52%) compared with the spring and summer seasons (36%), they were evenly distributed with gram-positive organisms during the winter and fall. CONCLUSION: A seasonal variation exists regarding the incidence of infection and causative organisms for posttraumatic wound infection following open extremity fractures. The incidence of infection is significantly higher in the spring and summer months with a preponderance of gram-positive organisms. Patients with infection after injuries sustained in the fall and winter months are more likely to have a Gustilo Grade 3 injury and gram-negative bacteria as the causative organism. LEVEL OF EVIDENCE: Epidemiologic study, level III.